S103 Changing prevalence of current asthma and inhaled corticosteroid treatment in the UK: population based cohort 2006 to 2016. (December 2018) - Bloom, CI; Feary, J; Jarvis, D; Saglani, S; Quint, JK
Abstract : Introduction and objectives: Asthma is a common in the UK, causing significant societal and healthcare burden. National prevalence estimates have been based on self-reported survey data from specific age-groups and geographical areas with relatively small sample sizes, or estimates of lifetime prevalence using electronic healthcare records. Here we estimate the prevalence of current disease, treatment and exacerbations, using the largest nationally representative database of primary care records (covering around 7% of the UK). Methods: We used 2006 to 2016 data in the Clinical Practice Research Datalink. We estimated the prevalence of current asthma by year, gender and age (<5, 5–11, 12–17, 18–24, 25–54 and ≥55 years), and the proportion 1) prescribed inhaled corticosteroid (ICS) and additional asthma-therapy, 2) treated for exacerbations, and 3) other asthma-care markers. Results: The overall prevalence of current asthma was 6.5% in 2016 (7.2% in 2006). Prevalence fell in all age groups under 45 years (no major changes in other age-groups). The lowest prevalence and largest absolute decrease was in those under 5 years. In 2016, 80% of current asthma patients were managed on an ICS (65% in 2006); this increase occurred in all ages, primarily due to an increase in low dose ICS (figure 1). Over the same period there was an increase in all age groups in the proportion prescribed additional asthma therapy, treated for an exacerbation in primary care, and recorded as having an annual asthma review and a management plan. Hospitalised exacerbations did not change significantly over time. Conclusions: Using doctor-diagnoses the prevalence of asthma in children and young-middle aged adults in the UK showed a small but significant decreases over the last ten years. Amongst those with a diagnosis there was an increase in prescriptions for ICS, additional asthma-therapy, treatment of exacerbations, and improvements in markers of quality of care. The decreasing prevalence may reflect a reticence to label milder disease as asthma, particularly in children under 5 years, where labels such as 'preschool wheeze' maybe more commonly used. Our findings could also reflect a trend towards more aggressive asthma management in primary care, including a lower threshold to treat exacerbations.